ANALISIS EFEK BEBAN KERJA DAN MOTIVASI BERPRESTASI TERHADAP PRODUKTIVITAS KERJA DENGAN MEMPERHATIKAN MEDIASI KEPUASAN KERJA [Studi Teller dan Customer Service PT Bank Negara Indonesia (Persero) Tbk Kantor: Cabang Brawijaya dan Cabang Malang] - Yohanes Christian Hadi Saputra; Rahayu Puji Suci; Nasharuddin Mas (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The purpose of this study was to obtain empirical evidence of workload and achievement motivation in encouraging increased work productivity, either directly or through the mediation of job satisfaction. This type of research is quantitative with the SEM-SmartPLS method. Data obtained through questionnaires distributed to 80 tellers and CS of PT Bank Negara Indonesia (Persero) Tbk Offices: Brawijaya Branch and Malang Branch. Empirical evidence shows that workload is not able to strongly influence work productivity, but workload has a strong effect on job satisfaction. Meanwhile, achievement motivation was able to encourage increased job satisfaction and work productivity. The mediation role of job satisfaction is also able to strongly mediate, both the effect of workload on work productivity, as well as the effect of achievement motivation on work productivity Tellers and CS PT Bank Negara Indonesia (Persero) Tbk Offices: Brawijaya Branch and Malang Branch.